UV (ultraviolet) resin as well as preparation method and application thereof
By preparing UV resin and polydimethylsiloxane diacrylate to form UV protection glue, the separation and puncture problems of insulating protection materials of new energy batteries are solved, and the effects of high bonding, temperature resistance, fire resistance and high insulation are achieved, improving the safety and reliability of the battery pack.
Patent Information
- Application Number
- CN202510874795.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-08-15
AI Technical Summary
The insulating protection materials of existing new energy batteries are easily separated and pierced when they are impacted by external forces for a long time, resulting in the risk of spontaneous combustion. The bonding strength and insulation of existing UV insulating adhesives are insufficient, making it difficult to meet the needs of high safety and high reliability.
UV resin is prepared by reacting the amine adduct of terminal isocyanate siloxane resin with isocyanate prepolymer, adding perfluorooctanol and hydroxyacrylate monomer, and preparing UV resin, using polydimethylsiloxane diacrylate as the reactive diluent, combining it into UV protective glue, adding flame retardant insulating fillers and additives to form a stable insulating protective film.
It improves the bonding performance, mechanical and mechanical properties, temperature resistance, fire resistance and electrical insulation of UV resin, reduces the risk of separation and puncture of the battery pack, and improves the safety and reliability of the battery pack.
Smart Images

Figure BDA0005470757310000021 
Figure BDA0005470757310000061 
Figure BDA0005470757310000071
Abstract
Description
Technical Field
[0001] The invention relates to a UV resin, a preparation method and application thereof, and belongs to the technical field of polymer materials. Background Art
[0002] New energy power batteries are primarily divided into battery packs, modules, and cells. As the core component and power source of new energy vehicles, battery packs are not only heavy but also complex in structure. They consist of multiple cell modules, each containing anywhere from a few to a dozen cells. Current and signal transmission between modules, between cells, and within the battery management system (BMS) that manages the cells requires various connections and current and temperature monitoring. External power transmission by the battery requires high-voltage connectors. Therefore, the reliability of cell and module connections, high- and low-voltage interfaces, and current and temperature monitoring is crucial. To achieve long battery life within a given battery size, the spacing between adjacent cells must be minimized. Therefore, insulating materials must be used between the cells to ensure a good seal and insulation, minimizing the risk of leakage and spontaneous combustion during prolonged exposure to high temperatures.
[0003] Blue-film pressure-sensitive tape, the current mainstream insulating protective material for new energy batteries, has been widely used in recent years, but its poor adhesion to new energy battery cells has been found. The experimental application of UV resin in insulating adhesives has pioneered a new approach to insulating adhesives for new energy batteries. Currently, small-scale commercial UV insulating adhesives are made from elastic polyurethane-modified UV resins, insulating fillers, diluent monomers, initiators, and other additives. Compared to blue-film, they offer superior bonding strength and insulation properties. However, while the addition of insulating fillers improves the insulating properties of UV insulating adhesives, they can easily cause separation and puncture of new energy battery packs when subjected to prolonged external impacts, thus increasing the risk of spontaneous combustion in collisions and reducing the safety of new energy batteries. Therefore, further optimization and breakthroughs are needed for insulating adhesives for new energy battery packs, particularly those requiring high temperature resistance, high insulation, high mechanical strength, and fire resistance. Summary of the Invention
[0004] In order to overcome the deficiencies of the prior art, the first object of the present invention is to provide a UV resin having good bonding properties, mechanical properties, temperature resistance, fire resistance, high electrical insulation, good heat aging resistance and chemical corrosion resistance.
[0005] The second object of the present invention is to provide a method for preparing the above-mentioned UV resin.
[0006] The third object of the present invention is to provide an application of the above-mentioned UV resin, in which the UV resin is used to prepare a UV protective adhesive, and polydimethylsiloxane diacrylate is used as a reactive diluent for compounding to play a role in heat insulation, flame retardancy and reinforcement.
[0007] The first object of the present invention can be achieved by adopting the following technical solution: a UV resin, wherein the raw materials for preparing the UV resin include the following active ingredients in parts by weight:
[0008]
[0009]
[0010] Furthermore, the isocyanate-terminated siloxane resin amine adduct is prepared by the following method: vacuum dehydrating the polyamine at a temperature of 100-120° C. for 2-4 hours, cooling to 30-60° C., adding the isocyanate-terminated siloxane and reacting for 3-8 hours to obtain the isocyanate-terminated siloxane amine adduct.
[0011] Further, the polyamine includes at least one of 4,4′-methylenebis(2-chloroaniline), diethyltoluenediamine, dimethylthiotoluenediamine, HMDA, MDA, DMDC, polyetheramine D230, polyetheramine T143, DDA, and piperazine.
[0012] Furthermore, the isocyanate-terminated siloxane is at least one of 3-isocyanatepropyltriethoxysilane and 3-isocyanatepropyltrimethoxysilane.
[0013] Furthermore, the isocyanate prepolymer is prepared by the following method: vacuum dehydrating the cashew nut shell oil phenolic resin polyol at a temperature of 100-120° C. for 2-4 hours, cooling to 65-95° C., adding isocyanate monomer and reacting for 3-8 hours to obtain the isocyanate prepolymer.
[0014] Further, the hydroxy acrylate monomer includes at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, pentaerythritol trimethacrylate and pentaerythritol triacrylate.
[0015] The second object of the present invention can be achieved by adopting the following technical solution: A method for preparing a UV resin, comprising:
[0016] Chain extension step: reacting 8-33 parts by weight of an isocyanate-terminated siloxane resin amine adduct and 20-50 parts by weight of an isocyanate prepolymer at a temperature of 30-80° C. for 1-3 hours;
[0017] End-capping step: adding 1-3 parts of perfluorooctanol and 3-15 parts of hydroxyacrylate monomer by weight, reacting at a temperature of 60-90° C. for 2-8 hours, and cooling to 40° C. to obtain UV resin.
[0018] The third object of the present invention can be achieved by adopting the following technical solution: a UV protective glue, the UV protective glue is prepared by the following method:
[0019] The polydimethylsiloxane diacrylate is dispersed and ground, and then the above-mentioned UV resin and auxiliary agent are added and dispersed evenly to obtain a UV protective adhesive.
[0020] Furthermore, polydimethylsiloxane diacrylate is prepared by the following method:
[0021] Mix dihydroxy polysiloxane with a molecular weight of 500, a polymerization inhibitor and a bifunctional BrФnsted-Lewis diacidic ionic liquid, heat to 120°C, add excess acrylic acid monomer dropwise, react for 6-36 hours, remove excess acrylic acid monomer and reaction water under reduced pressure, cool and filter to obtain polydimethylsiloxane diacrylate.
[0022] Furthermore, the auxiliary agent includes at least one of a flame retardant insulating filler, a photoinitiator, a dispersant, a defoaming agent, an antioxidant and a UV color paste.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The UV resin of the present invention has good bonding properties, mechanical properties, temperature resistance, fire resistance, high electrical insulation, good heat aging resistance and chemical corrosion resistance, and can overcome the problems of separation and puncture in battery cells;
[0025] 2. The UV protective adhesive of the present invention is compounded with polydimethylsiloxane diacrylate as an active diluent to play the role of heat insulation, flame retardancy and reinforcement. DETAILED DESCRIPTION
[0026] Below, in conjunction with specific embodiments, the present invention is further described:
[0027] The preparation of UV resin includes the following steps:
[0028] 1) Preparation of isocyanate-terminated siloxane resin amine adduct:
[0029] 7-15 parts of polyamine by weight are vacuum dehydrated at a temperature of 100-120° C. for 2-4 hours, cooled to 30-60° C., and 7-30 parts of terminal isocyanate siloxane are added and reacted for 3-8 hours to obtain a terminal isocyanate siloxane amine adduct.
[0030] The polyamine includes at least one of 4,4'-methylenebis(2-chloroaniline), diethyltoluenediamine, dimethylthiotoluenediamine, HMDA, MDA, DMDC, polyetheramine D230, polyetheramine T143, DDA and piperazine; and the UV resin is modified by terminal isocyanate siloxane to have better heat and fire resistance and better mechanical strength.
[0031] The isocyanate-terminated siloxane is at least one of 3-isocyanatepropyltriethoxysilane and 3-isocyanatepropyltrimethoxysilane.
[0032] 2) Preparation of isocyanate prepolymer:
[0033] 14-30 parts by weight of cashew nut shell oil phenolic resin polyol are vacuum dehydrated at a temperature of 100-120° C. for 2-4 hours, cooled to 65-95° C., and 7-20 parts of isocyanate monomer are added and reacted for 3-8 hours to obtain an isocyanate prepolymer.
[0034] The cashew nut shell oil phenolic resin polyol is at least one of Cardolite NX9001, NX9101, NX5285, NX9006 and NX9102, because the cashew nut shell oil phenolic resin polyol contains a plurality of phenolic structural units on the main chain, which can provide excellent mechanical strength and fire resistance.
[0035] 3) Preparation of UV resin:
[0036] Chain extension step: reacting 8-33 parts by weight of an isocyanate-terminated siloxane resin amine adduct and 20-50 parts by weight of an isocyanate prepolymer at a temperature of 30-80° C. for 1-3 hours;
[0037] End-capping step: adding 1-3 parts of perfluorooctanol and 3-15 parts of hydroxyacrylate monomer by weight, reacting at a temperature of 60-90° C. for 2-8 hours, cooling to 40° C., adding a polymerization inhibitor, and obtaining a UV resin.
[0038] The hydroxy acrylate monomer includes at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, pentaerythritol trimethacrylate and pentaerythritol triacrylate.
[0039] Among them, the introduction of perfluorooctanol provides better electrical insulation for UV resin.
[0040] Wherein, the polymerization inhibitor is at least one of benzoquinone, naphthoquinone, hydroquinone, catechol and p-hydroxyanisole.
[0041] 4) Preparation of polydimethylsiloxane diacrylate:
[0042] A dihydroxy polysiloxane with a molecular weight of 500, a polymerization inhibitor (p-hydroxyanisole), and a difunctionalized BrØnsted-Lewis diacidic ionic liquid are mixed, heated to 120°C, and an excess of acrylic acid monomer is added dropwise. The mixture is reacted for 6-36 hours. The excess acrylic acid monomer and reaction water are removed under reduced pressure and vacuum, and the mixture is cooled and filtered to obtain polydimethylsiloxane diacrylate. The reaction formula is shown in Formula I, and the structural formula of polydimethylsiloxane diacrylate is shown in Formula II.
[0043]
[0044]
[0045] UV resin is used to prepare UV protective glue:
[0046] The polydimethylsiloxane diacrylate is dispersed and ground, and then UV resin and auxiliary agents are added and dispersed evenly to obtain a UV protective adhesive.
[0047] The isocyanate prepolymer prepared from cashew nut shell oil phenolic resin polyol is used as the main reaction resin and compounded with high-temperature resistant polydimethylsiloxane diacrylate as an active diluent. The fluorine-modified isocyanate prepolymer with silane side chains has good bonding properties, mechanical properties, heat resistance, fire resistance, high electrical insulation, heat aging resistance, and chemical corrosion resistance. Polydimethylsiloxane diacrylate, a synergistic flame retardant, plays a role in thermal insulation and reinforcement. Under the action of a photoinitiator, it can be stably cross-linked. The prepared UV protective adhesive has good adhesion stability, insulation, impact resistance, heat resistance, and fire resistance, and can be used as a protective isolation material for battery cells in new energy battery packs.
[0048] The auxiliary agent includes at least one of a flame retardant insulating filler, a photoinitiator, a dispersant, a defoaming agent, an antioxidant and a UV color paste.
[0049] Among them, the flame retardant insulating filler is at least one of magnesium hydroxide-polyaluminum phosphate nanocomposite, aluminum hydroxide-polyaluminum phosphate nanocomposite, toluene phosphate-diphenyl ester doped nano-montmorillonite, tricresyl phosphate doped diatomaceous earth, tellurium compound, hydroxyaluminum, magnesium hydroxide and borate.
[0050] The photoinitiator is at least one of TPO, 184, 819, 369 and 1173.
[0051] Among them, the antioxidant is 1010.
[0052] The actual application scenario of UV protective glue is: first apply UV protective glue on the battery cell and light-curing it to form an insulating protective isolation film; then use UV protective glue to impregnate the reinforced carbon fiber elastic composite film and wrap it; then apply UV protective glue on the entire outside of the composite film.
[0053] Example 1:
[0054] Preparation of polydimethylsiloxane diacrylate:
[0055] A dihydroxy polysiloxane with a molecular weight of 500, a polymerization inhibitor (p-hydroxyanisole), and a difunctionalized BrØnsted-Lewis diacidic ionic liquid were mixed, heated to 120°C, and an excess of acrylic acid monomer was added dropwise. The mixture was allowed to react for 30 hours. The excess acrylic acid monomer and reaction water were removed under reduced pressure and vacuum, and the mixture was cooled and filtered to obtain polydimethylsiloxane diacrylate. The reaction formula is shown in Formula I, and the structural formula of polydimethylsiloxane diacrylate is shown in Formula II.
[0056]
[0057] Preparation Examples 2-7 obtained using Example 1:
[0058] Example 2:
[0059] The preparation of UV resin includes the following steps:
[0060] 1) Preparation of isocyanate-terminated siloxane resin amine adduct:
[0061] 267.2 g of 4,4'-methylenebis(2-chloroaniline) was vacuum dehydrated at 105°C for 2.5 h, cooled to 50°C, and 494 g of 3-isocyanatepropyltriethoxysilane was added and reacted for 5 h to obtain an isocyanate-terminated siloxane amine adduct.
[0062] 2) Preparation of isocyanate prepolymer:
[0063] 640 g of cashew nut shell oil phenolic resin polyol (Cardolite NX9001) was vacuum dehydrated at 115° C. for 2.5 h, cooled to 85° C., and 444.4 g of isocyanate monomer was added and reacted for 4 h to obtain an isocyanate prepolymer.
[0064] 3) Preparation of UV resin:
[0065] Chain extension step: reacting the isocyanate-terminated siloxane resin amine adduct and the isocyanate prepolymer at 50°C for 2 hours;
[0066] End-capping step: 72.8 g of perfluorooctanol and 234.4 g of hydroxyethyl methacrylate were added, reacted at 80° C. for 5 h, cooled to 40° C., and 0.45 g of hydroquinone was added to obtain a UV resin.
[0067] Example 3:
[0068] The preparation of UV resin includes the following steps:
[0069] 1) Preparation of isocyanate-terminated siloxane resin amine adduct:
[0070] 267.2 g of diethyltoluenediamine was vacuum dehydrated at 105° C. for 2.5 h, cooled to 50° C., and 494 g of 3-isocyanatepropyltrimethoxysilane was added and reacted for 5 h to obtain an isocyanate-terminated siloxane amine adduct.
[0071] 2) Preparation of isocyanate prepolymer:
[0072] 640 g of cashew nut shell oil phenolic resin polyol (Cardolite NX9001) was vacuum dehydrated at 115° C. for 2.5 h, cooled to 85° C., and 536 g of isocyanate monomer was added and reacted for 4 h to obtain an isocyanate prepolymer.
[0073] 3) Preparation of UV resin:
[0074] Chain extension step: reacting the isocyanate-terminated siloxane resin amine adduct and the isocyanate prepolymer at 50°C for 2 hours;
[0075] End-capping step: 72.8 g of perfluorooctanol and 234.4 g of hydroxyethyl methacrylate were added, reacted at 80° C. for 5 h, cooled to 40° C., and 0.45 g of hydroquinone was added to obtain a UV resin.
[0076] Example 2-3 is used to prepare UV protective glue, and the method is as follows:
[0077] At room temperature, 3 g of dispersant BYK110, 3 g of defoamer 6801, 50 g of polydimethylsiloxane diacrylate, and 100 g of magnesium hydroxide-polyaluminum phosphate nanocomposite were dispersed and ground at high speed to a particle size of less than 10 μm; then, UV resin, 10 g of antioxidant 1010, and 20 g of UV blue color paste were added to a disperser and dispersed evenly to obtain a UV protective adhesive.
[0078] Example 4:
[0079] The preparation of UV resin includes the following steps:
[0080] 1) Preparation of isocyanate-terminated siloxane resin amine adduct:
[0081] 214.4 g of dimethylthiotoluenediamine was vacuum dehydrated at 105° C. for 2.5 h, cooled to 50° C., and 494 g of 3-isocyanatepropyltriethoxysilane was added and reacted for 5 h to obtain an isocyanate-terminated siloxane amine adduct.
[0082] 2) Preparation of isocyanate prepolymer:
[0083] 640 g of cashew nut shell oil phenolic resin polyol (Cardolite NX9001) was vacuum dehydrated at 115° C. for 2.5 h, cooled to 85° C., and 444.4 g of isocyanate monomer was added and reacted for 4 h to obtain an isocyanate prepolymer.
[0084] 3) Preparation of UV resin:
[0085] Chain extension step: reacting the isocyanate-terminated siloxane resin amine adduct and the isocyanate prepolymer at 50°C for 2 hours;
[0086] End-capping step: 72.8 g of perfluorooctanol and 234.4 g of hydroxyethyl methacrylate were added, reacted at 80° C. for 5 h, cooled to 40° C., and 0.45 g of hydroquinone was added to obtain a UV resin.
[0087] Example 5:
[0088] The preparation of UV resin includes the following steps:
[0089] 1) Preparation of isocyanate-terminated siloxane resin amine adduct:
[0090] 267.2 g of 4,4'-methylenebis(2-chloroaniline) was vacuum dehydrated at 115°C for 2.5 h, cooled to 50°C, and 410 g of 3-isocyanatepropyltrimethoxysilane was added and reacted for 5 h to obtain an isocyanate-terminated siloxane amine adduct.
[0091] 2) Preparation of isocyanate prepolymer:
[0092] 640 g of cashew nut shell oil phenolic resin polyol (Cardolite NX9001) was vacuum dehydrated at 115° C. for 2.5 h, cooled to 85° C., and 444.4 g of isocyanate monomer was added and reacted for 4 h to obtain an isocyanate prepolymer.
[0093] 3) Preparation of UV resin:
[0094] Chain extension step: reacting the isocyanate-terminated siloxane resin amine adduct and the isocyanate prepolymer at 50°C for 2 hours;
[0095] End-capping step: 72.8 g of perfluorooctanol and 234.4 g of hydroxyethyl methacrylate were added, reacted at 80° C. for 5 h, cooled to 40° C., and 0.45 g of hydroquinone was added to obtain a UV resin.
[0096] Example 6:
[0097] The preparation of UV resin includes the following steps:
[0098] 1) Preparation of isocyanate-terminated siloxane resin amine adduct:
[0099] 267.2 g of 4,4'-methylenebis(2-chloroaniline) was vacuum dehydrated at 115°C for 2.5 h, cooled to 50°C, and 410 g of 3-isocyanatepropyltrimethoxysilane was added and reacted for 5 h to obtain an isocyanate-terminated siloxane amine adduct.
[0100] 2) Preparation of isocyanate prepolymer:
[0101] 267.2 g of cashew nut shell oil phenolic resin polyol (Cardolite NX9101) was vacuum dehydrated at 115° C. for 2.5 h, cooled to 85° C., and 536 g of isocyanate monomer was added and reacted for 4 h to obtain an isocyanate prepolymer.
[0102] 3) Preparation of UV resin:
[0103] Chain extension step: reacting the isocyanate-terminated siloxane resin amine adduct and the isocyanate prepolymer at 50°C for 2 hours;
[0104] End-capping step: 72.8 g of perfluorooctanol and 234.4 g of hydroxyethyl methacrylate were added, reacted at 80° C. for 5 h, cooled to 40° C., and 0.45 g of hydroquinone was added to obtain a UV resin.
[0105] Example 7:
[0106] The preparation of UV resin includes the following steps:
[0107] 1) Preparation of isocyanate-terminated siloxane resin amine adduct:
[0108] 267.2 g of 4,4'-methylenebis(2-chloroaniline) was vacuum dehydrated at 115°C for 2.5 h, cooled to 50°C, and 410 g of 3-isocyanatepropyltrimethoxysilane was added and reacted for 5 h to obtain an isocyanate-terminated siloxane amine adduct.
[0109] 2) Preparation of isocyanate prepolymer:
[0110] 640 g of cashew nut shell oil phenolic resin polyol (Cardolite NX9001) was vacuum dehydrated at 115° C. for 2.5 h, cooled to 85° C., and 536 g of isocyanate monomer was added and reacted for 4 h to obtain an isocyanate prepolymer.
[0111] 3) Preparation of UV resin:
[0112] Chain extension step: reacting the isocyanate-terminated siloxane resin amine adduct and the isocyanate prepolymer at 50°C for 2 hours;
[0113] End-capping step: 72.8 g of perfluorooctanol and 437 g of pentaerythritol triacrylate were added, reacted at 80° C. for 5 h, cooled to 40° C., and 0.45 g of hydroquinone was added to obtain a UV resin.
[0114] Examples 4-7 are used to prepare UV protective adhesives, and the method is as follows:
[0115] At room temperature, 3 g of dispersant BYK110, 3 g of defoamer 6801, 50 g of polydimethylsiloxane diacrylate, and 100 g of magnesium hydroxide-polyaluminum phosphate nanocomposite were dispersed and ground at high speed to a particle size of less than 10 μm; then 814 g of UV resin, 10 g of antioxidant 1010, and 20 g of UV blue color paste were added to a disperser and dispersed evenly. The mixture was stirred for 1 hour under a vacuum condition of -0.8 MPa, and then kept warm at 35°C for 1 hour to prepare a UV protective adhesive.
[0116] Comparative Example 1:
[0117] At room temperature, 3 g of dispersant BYK110, 3 g of defoamer 6801, 50 g of isobornyl acrylate, and 100 g of magnesium hydroxide-aluminum polyphosphate nanocomposite were dispersed and ground at high speed to a particle size of less than 10 μm; then 814 g of commercially available polyurethane acrylic resin Allnex resin EBECRYL 4491, 10 g of antioxidant 1010, and 20 g of UV blue color paste were added to a disperser and dispersed evenly. The mixture was stirred for 1 hour under a vacuum condition of -0.8 MPa, and then kept warm at 35°C for 1 hour to prepare a UV protective adhesive.
[0118] Comparative Example 2:
[0119] At room temperature, 3 g of dispersant BYK110, 3 g of defoamer 6801, 50 g of polysiloxane diacrylate, and 100 g of magnesium hydroxide-polyaluminum phosphate nanocomposite were dispersed and ground at high speed to a particle size of less than 10 μm; then 814 g of commercially available polyurethane acrylic resin Allnex resin EBECRYL 4491, 10 g of antioxidant 1010, and 20 g of UV blue color paste were added to a disperser and dispersed evenly. The mixture was stirred for 1 hour under a vacuum condition of -0.8 MPa, and then kept warm at 35°C for 1 hour to prepare a UV protective adhesive.
[0120] Detection:
[0121] Performance Test The following performance tests were conducted on the UV protective adhesives prepared in Examples 2-7 and the UV insulating protective adhesives for new energy batteries prepared in Comparative Examples 1-2:
[0122] 1. Adhesion stability test:
[0123] Apply UV protective glue at 50g / m2 The coating amount was applied to the stainless steel test plate, and then cured for 15 seconds under an LED UV lamp with a wavelength of 395nm. After being placed at 25℃ for 2 hours, it was placed in a constant temperature and humidity chamber with a temperature of 85℃ and a humidity of 85% for 42 days (1008 hours). The adhesion of the UV insulation protective glue was tested using the 100-grid test method, and the test results were tested and recorded.
[0124] 2. Insulation test:
[0125] According to the test method of GB / T 1408.1-2016, use a voltage breakdown tester to test the dielectric strength (unit: KV / mm) of the UV protective adhesive, and test and record the test results.
[0126] 3. Impact resistance test:
[0127] According to the test method in GB / T 1732-2020, the impact strength of the UV protective adhesive was tested. The results were expressed as the maximum height (unit: cm) at which no cracks, wrinkles or peeling were observed in three parallel tests. The test results were tested and recorded.
[0128] 4. Salt spray resistance test:
[0129] Apply UV insulation protective glue at 50g / m 2 Apply the coating amount on the stainless steel test plate and use standard neutral salt spray to test at a temperature of 35°C. When corrosion or discoloration occurs on the surface of the UV insulation protective adhesive, record the test time (unit: h).
[0130] 5. Flame retardancy test:
[0131] The UV protective adhesive was tested according to GB / T 2408-2008 "Determination of the flammability of coatings such as radial logistics, ceramic tiles, corrugated pipes, etc. - Vertical burning method".
[0132] Flame retardant grades are divided into:
[0133] 1.N grade: non-flame retardant
[0134] 2. FV0: vertical burning does not exceed 10s, and the burning length does not exceed 50mm
[0135] 3. FV1: vertical burning does not exceed 15s, and the burning length does not exceed 150mm
[0136] 4. FV2: vertical burning does not exceed 30s, and the burning length does not exceed 200mm
[0137] 5. FV3: vertical burning does not exceed 60s, and the burning length does not exceed 300mm
[0138] 6. FV4: vertical burning time does not exceed 120s, and burning length does not exceed 400mm
[0139] The following are the test data of adhesion stability, insulation and impact resistance of the UV protective glue for new energy batteries prepared in Examples 2-7 and Comparative Example 1, as shown in Table 1.
[0140] Table 1 Adhesion stability, insulation and impact resistance test results of Examples 2-7 and Comparative Examples 1-2
[0141]
[0142] It can be seen from the detection of the UV protective glue of Examples 2-7 and the comparative examples that the UV protective glue using this solution has good adhesion stability, insulation, impact resistance and flame retardancy. The adhesion can reach 5B after 1008h of the double 85 test, the impact test height is increased from 16cm to 56cm, and the salt spray corrosion resistance can reach 610h. It is not easy to separate, fall off and puncture when applied to new energy batteries. Example 2-7 is better than the current mainstream polyurethane acrylic resin. The difference between Comparative Example 1-2 is that Comparative Example 1 does not use polydimethylsiloxane diacrylate, and Comparative Example 2 adds polydimethylsiloxane diacrylate, which introduces high-temperature resistant polysiloxane and multi-side methyl groups into the protective glue segment, further improving the fire retardancy, dielectric strength and adhesion of the protective glue. The cashew nut shell oil phenolic resin polyol and silicon-modified polyamine used in Examples 2-7 have better fire retardancy, and the polydimethylsiloxane diacrylate prepared at the same time can further improve the adhesion stability, insulation and impact resistance of the prepared UV protective adhesive.
[0143] Those skilled in the art can make various other corresponding changes and modifications based on the technical solutions and concepts described above, and all of these changes and modifications should fall within the scope of protection of the claims of the present invention.
Claims
1. A UV resin, characterized in that: The raw materials for preparing the UV resin include the following active ingredients in parts by weight:
2. The UV resin according to claim 1, wherein The isocyanate-terminated siloxane resin amine adduct is prepared by the following method: vacuum dehydrating a polyamine at a temperature of 100-120° C. for 2-4 hours, cooling to 30-60° C., adding an isocyanate-terminated siloxane and reacting for 3-8 hours to obtain the isocyanate-terminated siloxane amine adduct.
3. The UV resin according to claim 2, wherein The polyamine includes at least one of 4,4'-methylenebis(2-chloroaniline), diethyltoluenediamine, dimethylthiotoluenediamine, HMDA, MDA, DMDC, polyetheramine D230, polyetheramine T143, DDA and piperazine.
4. The UV resin according to claim 2, wherein The isocyanate-terminated siloxane is at least one of 3-isocyanatepropyltriethoxysilane and 3-isocyanatepropyltrimethoxysilane.
5. The UV resin according to claim 1, wherein The isocyanate prepolymer is prepared by the following method: vacuum dehydrating cashew nut shell oil phenolic resin polyol at a temperature of 100-120° C. for 2-4 hours, cooling to 65-95° C., adding isocyanate monomer and reacting for 3-8 hours to obtain the isocyanate prepolymer.
6. The UV resin according to claim 1, wherein The hydroxy acrylate monomer includes at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, pentaerythritol trimethacrylate and pentaerythritol triacrylate.
7. A method for preparing UV resin, characterized in that: include: Chain extension step: reacting 8-33 parts by weight of an isocyanate-terminated siloxane resin amine adduct and 20-50 parts by weight of an isocyanate prepolymer at a temperature of 30-80° C. for 1-3 hours; End-capping step: adding 1-3 parts of perfluorooctanol and 3-15 parts of hydroxyacrylate monomer by weight, reacting at a temperature of 60-90° C. for 2-8 hours, and cooling to 40° C. to obtain UV resin.
8. A UV protective adhesive, characterized in that: The UV protective glue is prepared by the following method: Polydimethylsiloxane diacrylate is dispersed and ground, and then the UV resin and the auxiliary agent as claimed in any one of claims 1 to 7 are added and dispersed evenly to obtain a UV protective adhesive.
9. The UV protective adhesive according to claim 8, characterized in that: The polydimethylsiloxane diacrylate is prepared by the following method: Mix dihydroxy polysiloxane with a molecular weight of 500, a polymerization inhibitor and a bifunctional BrФnsted-Lewis diacidic ionic liquid, heat to 120°C, add excess acrylic acid monomer dropwise, react for 6-36 hours, and remove excess acrylic acid monomer and reaction water under reduced pressure and vacuum to obtain polydimethylsiloxane diacrylate.
10. The UV protective adhesive according to claim 8, characterized in that: The auxiliary agent comprises at least one of a flame retardant insulating filler, a photoinitiator, a dispersant, a defoaming agent, an antioxidant and a UV color paste.